Evaluation of BiliCare™ transcutaneous bilirubin device in Japanese newborns. Issue 10 (31st August 2017) - Yamana, Keiji; Morioka, Ichiro; Kurokawa, Daisuke; Fukushima, Sachiyo; Nishida, Kosuke; Ohyama, Shohei; Nishimura, Noriyuki; Nozu, Kandai; Taniguchi‐Ikeda, Mariko; Nagase, Hiroaki; Fujioka, Kazumichi; Iwatani, Sota; et al.
Abstract: Background: Non‐invasive transcutaneous bilirubin (TcB) monitoring has been widely used to screen for hyperbilirubinemia. TcB measured using the recently developed BiliCare™ system, however, has not been fully evaluated. Methods: One hundred and seven TcB measurements were obtained from 82 Japanese newborns ≥35 weeks' gestational age within 2 weeks after birth. Measurements were taken at the scaphoid fossa, conchal cavity, and lobe of the ear using BiliCare. BiliCare TcB were compared with total serum bilirubin (TB) and TcB obtained using another bilirubinometer (JM‐105™). Results: Transcutaneous bilirubin measured at all three sites significantly correlated with TB ( r = 0.91, 0.93, and 0.93 at the scaphoid fossa, conchal cavity, and lobe, respectively). The mean differences were 0.1, −0.3, and 3.6 at the scaphoid fossa, conchal cavity, and lobe, respectively. BiliCare TcB at the scaphoid fossa significantly correlated with that using the JM‐105 ( r = 0.91). The mean difference was 0.0. BiliCare, however, produced a significantly higher and lower TcB than the JM‐105 for TB <7 and ≥15 mg/dL, respectively. Conclusions: Transcutaneous bilirubin measurements taken at the scaphoid fossa or conchal cavity using BiliCare were more reliable than those at the earlobe. BiliCare TcB differed from those of the JM‐105, for TB <7 or ≥15 mg/dL.